2008
DOI: 10.1007/s10096-008-0602-7
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal carriage of Staphylococcus aureus: how does its frequency compare with that of nasal carriage and what is its clinical impact?

Abstract: The bacterial species Staphylococcus aureus, including its methicillin-resistant variant (MRSA), finds its primary ecological niche in the human nose, but is also able to colonize the intestines and the perineal region. Intestinal carriage has not been widely investigated despite its potential clinical impact. This review summarizes literature on the topic and sketches the current state of affairs from a microbiological and infectious diseases' perspective. Major findings are that the average reported detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 95 publications
(93 reference statements)
6
171
1
2
Order By: Relevance
“…With an aim to expand the application potential of these strains, it was envisaged that determination of the adhesion potential of the strains to the ECM would be pertinent, as adhesion to ECM molecules such as collagen and mucin is considered as a cardinal feature of probiotic strains (Lebeer et al, 2008). The ability of the pathogen S. aureus to colonize the intestine in conjunction with its ability to adhere to ECM molecules is a serious healthcare concern and has been reported to be responsible for various ailments (Acton et al, 2009;Bhalla et al, 2007;Foster et al, 2014;Gries et al, 2005;Hansen et al, 2006). In this context, probiotic LAB strains having a propensity to adhere onto the ECM such as collagen and mucin could bear interesting therapeutic potential to prevent invasion of the ECM by S. aureus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an aim to expand the application potential of these strains, it was envisaged that determination of the adhesion potential of the strains to the ECM would be pertinent, as adhesion to ECM molecules such as collagen and mucin is considered as a cardinal feature of probiotic strains (Lebeer et al, 2008). The ability of the pathogen S. aureus to colonize the intestine in conjunction with its ability to adhere to ECM molecules is a serious healthcare concern and has been reported to be responsible for various ailments (Acton et al, 2009;Bhalla et al, 2007;Foster et al, 2014;Gries et al, 2005;Hansen et al, 2006). In this context, probiotic LAB strains having a propensity to adhere onto the ECM such as collagen and mucin could bear interesting therapeutic potential to prevent invasion of the ECM by S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the gut-colonizing pathogens, emerging literature reports have elucidated the detrimental implications of colonization by Staphylococcus aureus (Acton et al, 2009;Yan et al, 2014). S. aureus is known to be equipped with adhesins known as microbial surface component-recognizing adhesive matrix molecules for binding to ECM molecules such as collagen (Foster et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, we are confident that we have captured the majority of carriage by screening an additional body site (groin) in contrast to most previous studies cited above. Groin swab was chosen to detect patients with gastrointestinal MRSA carriage 39 and to increase the yield of nasal screening only. 40 We have previously determined at our institution that the addition of throat screening did not significantly improve the accuracy of detecting MRSA colonization.…”
Section: Discussionmentioning
confidence: 99%
“…By including screening cultures from the throat the sensitivity of detecting colonization significantly increases and it has therefore been suggested that S. aureus screening programs should include sampling of the anterior nares as well as the throat (Mertz et al 2007). Other anatomical sites, e.g., the axilla, groin, skin and the intestinal tract, are also colonized with S. aureus (Acton et al 2009;Vento et al 2013) S. aureus nasal carriers are usually divided into three distinct groups (Gould & McKillop 1954;Kluytmans et al 1997). …”
Section: Carriage and Colonizationmentioning
confidence: 99%